1997
DOI: 10.1007/s002849900166
|View full text |Cite
|
Sign up to set email alerts
|

Purification of Glucoamylase from Lactobacillus amylovorus ATCC 33621

Abstract: An intracellular glucoamylase (E.C. 3.2.1.3) was purified to homogeneity from Lactobacillus amylovorus on a Fast Protein liquid chromatography System (FPLC) with a Mono Q ion-exchanger and two Superose 12 gel filtration columns arranged in series. The enzyme activity was quantified with a specific, chromogenic substrate, p-nitrophenyl-beta-maltoside. Preparative gel electrophoresis was then used to further purify active enzyme fractions. Native polyacrylamide gel electrophoresis (Native-PAGE) and sodium dodecy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 34 publications
1
13
0
1
Order By: Relevance
“…The compositions of monosaccharide in EPSs were analyzed with the alditol acetate derivatization method, using GC-MS. 23) After the purified EPS (5 mg) was hydrolyzed with 2 M trifluoroacetic acid at 120°C for 1 h to obtain each monosaccharide, the reduced reaction was performed, followed by acetylation. The resulting derivative was analyzed by GC-MS, using a JMS-T100GCV AccuTOF GCv 4G gas chromatograph high-resolution time-of-flight mass spectrometer (JEOL, Tokyo, Japan) equipped with a source of ions for electron ionization (EI), using a DB-WAX capillary column (0.25 mm×0.25 µm×30 m) (Agilent, Santa Clara, CA, U.S.A.).…”
Section: Analysis Of Constitution Sugars In Epssmentioning
confidence: 99%
“…The compositions of monosaccharide in EPSs were analyzed with the alditol acetate derivatization method, using GC-MS. 23) After the purified EPS (5 mg) was hydrolyzed with 2 M trifluoroacetic acid at 120°C for 1 h to obtain each monosaccharide, the reduced reaction was performed, followed by acetylation. The resulting derivative was analyzed by GC-MS, using a JMS-T100GCV AccuTOF GCv 4G gas chromatograph high-resolution time-of-flight mass spectrometer (JEOL, Tokyo, Japan) equipped with a source of ions for electron ionization (EI), using a DB-WAX capillary column (0.25 mm×0.25 µm×30 m) (Agilent, Santa Clara, CA, U.S.A.).…”
Section: Analysis Of Constitution Sugars In Epssmentioning
confidence: 99%
“…᭺, ␣-amylase activity; ᭡, cell count (cfu/ ml). and became constant after 40 h. Glucoamylase activity was not detected by the method of James et al (1997) throughout the experiments, suggesting that only a minimal amount of the enzyme was synthesized to supply glucose to the cells. Production of lactic acid and pH of the culture broth followed the change in ␣-amylase activity.…”
Section: Resultsmentioning
confidence: 94%
“…Lactobacillus amylovorus, a member of the L. acidophilus-group, is one of these amylolytic species (Nakamura, 1981). ␣-Amylase and glucoamylase produced by the type strain of L. amylovorus have been characterized in detail (Giraud & Cuny, 1997;James et al, 1997). We previously compared ten strains of L. amylovorus with respect to lactic acid fermentation from starch and found that strain JCM 10628 produced lactic acid from raw cornstarch at a much higher rate than other strains (Oda et al, 2000).…”
mentioning
confidence: 99%
“…Microbial strains and culture media [4]. One unit of the enzyme activity was defined at the amount of enzyme which releases 100 μg of glucose from soluble starch for 1 hr under the above condition.…”
Section: Methodsmentioning
confidence: 99%
“…Rhizomucor pusilus and Endomyces sp. [4,5,16] In the yeast, Sacchoromyces diastaticus, three isoenzymes of the extracellular glucoamylase have been reported; glucoamylase I, glucoamylase II and glucoamylase III. These isozymes are encoded by the STA1 (DEX2), STA2 (DEX1) and STA3 (DEX3) gene, respectively [14].…”
Section: Introductionmentioning
confidence: 99%